Strong convergence theorems by hybrid projection methods for equilibrium problems and fixed point problems of the asymptotically quasi-ϕ-nonexpansive mappings - Kim, Jong Kyu (Fixed point theory and applications (Hindawi Publishing Corporation), 2011)
We consider a hybrid projection method for finding a common element in the fixed point set of an asymptotically quasi- ϕ -nonexpansive mapping and in the solution set of an equilibrium problem. Strong convergence theorems of common elements are established in a uniformly smooth and strictly convex Banach space which has the Kadec-Klee property. 2000 Mathematics subject classification : 47H05, 47H09, 47H10, 47J25